Estimates of Smoking before and during Pregnancy, and Smoking Cessation during Pregnancy: Comparing Two Population-Based Data Sources. (May 2013) - Tong, Van T.; Dietz, Patricia M.; Farr, Sherry L.; D'Angelo, Denise V.; England, Lucinda J.
Objectives: We compared three measures of maternal smoking status—prepregnancy, during pregnancy, and smoking cessation during pregnancy—between the Pregnancy Risk Assessment Monitoring System (PRAMS) questionnaire and the 2003 revised birth certificate (BC). Methods: We analyzed data from 10, 485 women with live births in eight states from the 2008 PRAMS survey, a confidential, anonymous survey administered in the postpartum period that is linked to select BC variables. We calculated self-reported prepregnancy and prenatal smoking (last trimester only) prevalence based on the BC, the PRAMS survey, and the two data sources combined, and the percentage of smoking cessation during pregnancy based on the BC and PRAMS survey. We used two-sided t-tests to compare BC and PRAMS estimates. Results: Prepregnancy smoking prevalence estimates were 17.3% from the BC, 24.4% from PRAMS, and 25.4% on one or both data sources. Prenatal smoking prevalence estimates were 11.3% from the BC, 14.0% from PRAMS, and 15.2% on one or both data sources. The percentages of prepregnancy smokers who indicated that they quit smoking by the last trimester were 35.1% from the BC and 42.6% from PRAMS. The PRAMS estimates of prepregnancy and prenatal smoking, and smoking cessation during pregnancy were statistically higher than the corresponding BC estimates (t-tests, p <0.05). Conclusions: PRAMS captured more women who smoked before and during the last trimester than the revised BC. States implementing PRAMS and the revised BC should consider information from both sources when developing population-based estimates of smoking before pregnancy and during the last trimester of pregnancy.